Discovery of rare coding variants in OGDHL and BRCA2 in relation to breast cancer risk in Chinese women. Issue 8 (27th December 2019) - Guo, Xingyi; Long, Jirong; Chen, Zhishan; Shu, Xiao‐ou; Xiang, Yong‐Bing; Wen, Wanqing; Zeng, Chenjie; Gao, Yu‐Tang; Cai, Qiuyin; Zheng, Wei
Abstract : The missing heritability of breast cancer could be partially attributed to rare variants (MAF < 0.5%). To identify breast cancer‐associated rare coding variants, we conducted whole‐exome sequencing (~50×) in genomic DNA samples obtained from 831 breast cancer cases and 839 controls of Chinese females. Using burden tests for each gene that included rare missense or predicted deleterious variants, we identified 29 genes showing promising associations with breast cancer risk. We replicated the association for two genes, OGDHL and BRCA2, at a Bonferroni‐corrected p < 0.05, by genotyping an independent set of samples from 1, 628 breast cancer cases and 1, 943 controls. The association for OGDHL was primarily driven by three predicted deleterious variants (p.Val827Met, p.Pro839Leu, p.Phe836Ser; p < 0.01 for all). For BRCA2, we characterized a total of 27 disruptive variants, including 18 nonsense, six frameshift and three splicing variants, whereas they were only detected in cases, but none of the controls. All of these variants were either very rare (AF < 0.1%) or not detected in >4, 500 East Asian women from the genome Aggregation database (gnomAD), providing additional support to our findings. Our study revealed a potential novel gene and multiple disruptive variants of BRCA2 for breast cancer risk, which may identify high‐risk women in Chinese populations. Abstract : What's new? Many rare pathogenic coding variants in breast cancer have recently been discovered by sequencing known cancer predisposition genes in European‐ancestry populations. However, rare coding variants in known breast cancer susceptibility genes and other less well‐characterized genes have not been adequately investigated in Asian populations. Using both whole‐exome sequencing and array‐based genotyping approaches, here the authors identified OGDHL as a novel breast cancer susceptibility gene and multiple disruptive variants of BRCA2 in Chinese women. The identification of variants associated with an elevated risk of breast cancer has important implications in genetic testing to identify high‐risk women to reduce breast cancer risk.